Trans-cinnamaldehyde protects against phenylephrine-induced cardiomyocyte hypertrophy through the CaMKII/ERK pathway - Dongdong Qian; Jing Tian; Sining Wang; Xiaoli Shan; Pei Zhao; Huihua Chen; Ming Xu; Wei Guo; Chen Zhang; Rong Lu (BMC, 2022)
Abstract Background Trans-cinnamaldehyde (TCA) is one of the main pharmaceutical ingredients of Cinnamomum cassia Presl, which has been shown to have therapeutic effects on a variety of cardiovascular diseases. This study was carried out to characterize and reveal the underlying mechanisms of the protective effects of TCA against cardiac hypertrophy. Methods We used phenylephrine (PE) to induce cardiac hypertrophy and treated with TCA in vivo and in vitro. In neonatal rat cardiomyocytes (NRCMs), RNA sequencing and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were carried out to identify potential pathways of TCA. Then, the phosphorylation and nuclear localization of calcium/calmodulin-dependent protein kinase II (CaMKII) and extracellular signal-related kinase (ERK) were detected. In adult mouse cardiomyocytes (AMCMs), calcium transients, calcium sparks, sarcomere shortening and the phosphorylation of several key proteins for calcium handling were evaluated. For mouse in vivo experiments, cardiac hypertrophy was evaluated by assessing morphological changes, echocardiographic parameters, and the expression of hypertrophic genes and proteins. Results TCA suppressed PE-induced cardiac hypertrophy and the phosphorylation and nuclear localization of CaMKII and ERK in NRCMs. Our data also demonstrate that TCA blocked the hyperphosphorylation of ryanodine receptor type 2 (RyR2) and phospholamban (PLN) and restored Ca2+ handling and sarcomere shortening in AMCMs. Moreover, our data revealed that TCA alleviated PE-induced cardiac hypertrophy in adult mice and downregulated the phosphorylation of CaMKII and ERK. Conclusion TCA has a protective effect against PE-induced cardiac hypertrophy that may be associated with the inhibition of the CaMKII/ERK pathway.